2023
DOI: 10.1002/ajh.26938
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and clinicopathologic characterization of pediatric histiocytoses

Abstract: The spectrum of somatic mutations in pediatric histiocytoses and their clinical implications are not fully characterized, especially for non-Langerhans cell histiocytosis (-LCH) subtypes. A cohort of 415 children with histiocytosis from the French histiocytosis registry was reviewed and analyzed for BRAF V600E . Most BRAF WT samples were analyzed by next-generation sequencing (NGS) with a custom panel of genes for histiocytosis and myeloid neoplasia. Of 415 case samples, there were 366 LCH, 1 Erdheim-Chester d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Our data showed that BRAF V600E mutation was associated with multicentric disease and risk organ involvement. This phenotype is in line with pediatric LCH ( 6 ) ( 7 ) studies and ECD cohort ( 8 ). Excluding RDD patients, the presence of BRAF V600E correlated with risk organ involvement irrespective of the type of “L-group histiocytosis”.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our data showed that BRAF V600E mutation was associated with multicentric disease and risk organ involvement. This phenotype is in line with pediatric LCH ( 6 ) ( 7 ) studies and ECD cohort ( 8 ). Excluding RDD patients, the presence of BRAF V600E correlated with risk organ involvement irrespective of the type of “L-group histiocytosis”.…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly the genetic landscape analysis of various cancers, such as melanoma, colon cancer, lung cancer, and more recently histiocytic neoplasms, has highlighted the pivotal role of BRAF V600E gene, which is considered an important cornerstone in the development of human cancer. Its presence is associated with disseminated disease, neurodegeneration, and resistance to front-line therapy in pediatric LCH patients ( 6 , 7 ). In adults, LCH is mainly restricted to the lung, making BRAF V600E testing difficult due to the risk of a pulmonary biopsy procedure and a low DNA quantity when available.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, genomic studies have been conducted on histiocytosis, including JXG, and distinctive genetic abnormalities have been discovered (e.g., BRAFV600E mutations and ALK translocations). 4 , 5 These novel genetic discoveries further confirmed the tumorigenesis of JXG and highlighted the possibility of therapeutic targets in refractory or severe cases.…”
mentioning
confidence: 78%
“…At the origin of these diseases is a clonal proliferation of cells that morphologically and immunophenotypically resemble macrophage line cells. Excessive activation of the RAS/ /mitogen-activated protein kinases (MAPK) signaling pathway lies at the base of the pathomechanism [2,4,5]. The current classification divides histiocytosis into five groups: C, H, L, M and R.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the management of LCH can vary greatly from a 'wait-and-watch' attitude through serious procedures such as intensive chemotherapy up to bone marrow stem cell transplantation. In LCH, BRAF V600E is the most frequently detected mutation, followed by MAP2K1 alterations [1,2,5,7,8]. The occurrence of mutations seems to cause a more severe course and resistance to conventional chemotherapy, with potentially higher mortality and severe secondary conditions such as neurodegenerative disease (ND) or sclerosing cholangitis (SC) with consequent liver cirrhosis [7,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%